Radiation effect on MHD blood flow through a tapered porous stenosed artery with thermal and mass diffusion - Sharma, Madhu; Gaur, Rajarshi; Sharma, Bhupendra K. (Zielona Góra: Uniwersytet Zielonogórski)
A mathematical model for MHD blood flow through a stenosed artery with Soret and Dufour effects in the presence of thermal radiation has been studied. A uniform magnetic field is applied perpendicular to the porous surface. The governing non-linear partial differential equations have been transformed into linear partial differential equations, which are solved numerically by applying the explicit finite difference method.
Keywords: Soret effect; Dufour effect; MHD; blood flow; stenosis; chemical reaction